Successful Repair of a Complete Atrioventricular Septal Defect Associated with Transposition of the Great Arteries: A Rare Association and a Literature Review - F, Torchio; M, Lo Rito; E, Bergonzoni; A, Gaspari; A, Giamberti (Archives of Clinical and Medical Case Reports, 2024)
Complete atrioventricular septal defect associated with transposition of the great arteries is a relatively rare congenital heart disease, with only a few cases reported in the literature. Surgical strategy between one-stage or two-stage repair represents a challenging decision-making process. Herein, we report the case of an 11-month-old infant who received a postnatal diagnosis of a complete type A atrioventricular septal defect associated with malposition of the great arteries. The patient underwent a successful one-stage anatomic repair with arterial switch procedure and cAVSD repair with a two-patch technique. His post-operative course was uneventful and the patient was discharged home in stable condition. This case highlights the suitability of one-stage surgical repair in infants with cAVSD and TGA, resulting in successful outcomes with few complications.